Analysis on Preparation, Application, and Recycling of Activated Carbon to Aid in COVID-19 Protection - Reza, Md Sumon; Hasan, ABM Kamrul; Afroze, Shammya; Bakar, Muhammad S. Abu; Taweekun, Juntakan; Azad, Abul K. (International Journal of Integrated Engineering, 2020)
Activated carbon (AC) is an extremely porous carbonaceous adsorptive substance which has a rigid carbon matrix with high surface area and broad functional groups. The structure is connected by chemical bonds; arranged irregularly, generating a highly porous arrangement of corners, crevices, claps, and cracks between the carbon layers. Activated carbons are produced high-temperature and chemical activation of waste biomass. The pores in the lattice network of activated carbon permit the removal of impurities from gaseous and liquid medium through adsorption. At present, the COVID-19 disease is the prime concern around the whole world because of its exponential infections and death rate. There is no medicine for this virus, and protection is the only remedy to survive from this contagious disease. Using a face mask is one of the best methods to get rid of COVID-19. The mask combined with activated carbon can be beneficial for adsorbing and disinfecting the virus as it is the versatile adsorbent for the elimination of the organic, inorganic, and pathogenic contaminants.